O roteirista Cesare Zavattini: método e estrutura narrativa do filme Umberto D. - Joana Pires Mascarenhas Ribeiro de Oliveira (2017)
This research investigates and reflects on the method of work, the creative process and the procedures adopted by italian neorealist writer Cesare Zavattini (1902-1989), to write the screenplay for the film Umberto D. (Italy, 1952), directed by Vittorio De Sica. The texts of the entire creative process of Zavattini in the writing of the film were published at the time,Dal soggetto ala sceneggiatura. Come si scrive un capolavoro: Umberto D., provides material for an analysis from the first draft of the cinematographic idea until its transformation into script is made. The narrative innovations brought by Cesare Zavattini to film making receive a new appreciation.